Analysis of drainage pattern and its relationship with gold potential in Batu Melintang, Jeli, Kelantan. Issue 1 (August 2021) - Sulaiman, M S; Udin, W S; Khan, M A; Sulaiman, N; Ismail, R; Bahar, A
Abstract: The study is conducted within approximately 42km 2 in the northern Kelantan, specifically at Batu Melintang, Jeli. The study aims to analyze drainage and its relationship with gold potential. The lithology of the study area consists of metasedimentary, metamorphic and igneous rock. Sungai Pergau and Sungai Tadoh are the main rivers fed by tributary drainages located in the highly potential gold zones. It is important to understand the relationship of the potential gold zones with the drainage system because if any exploitation of the drainage system occurs, it could disrupt the main river system. This research was conducted using the geological gridded sampling method followed by the fire assay method to detect gold. Drainage analysis is conducted using satellite imagery and ArcGIS software. The result shows that Grid 1, 2 and 3 show the highest gold potential, whereas grid 7, 8 and 9 show the lowest gold potential. The drainage analysis shows the majority of the drainage pattern is trellis type and only grid 2 with rectangular and grid 9 with dendritic type. The study also found that the lowest drainage coverage (8052m) is in grid 2, which has the highest gold intensity. In contrast, the highest drainage coverage (15032m) is in grid 9, with the lowest gold potential.